STRATEGI INOVATIF PENGELOLAAN RISIKO BENCANA HIDROMETEOROLOGI : OPTIMALISASI SISTEM DRAINASE BERWAWASAN LINGKUNGAN (EKODRAINASE) DALAM MENCEGAH BANJIR DAN LIMPASAN PADA ADAPTASI PERUBAHAN IKLIM DI KABUPATEN KARAWANG - Bahar Amal; Dicki Dian Purnama; Fatma Nurkhaerani; Alipia Pebrian; Farda Mariam Al Jamilah (LPPM Universitas Negeri Jakarta, 2024)
Urban drainage is a network system for waste disposal in urban areas that functions to manage or control surface water, so that it does not disrupt or harm the community and provides benefits for human activities. This research aims to create synergy and steps for the implementation of eco-drainage in the urban characteristic conditions of Karawang Regency. The method used involves data collection through observation, interviews, historical data analysis, and mapping based on SNI Number 02-2406-1991 regarding the General Planning Procedures for Urban Drainage. The research results indicate that the Eco drain infrastructure consists of 7 elements, namely rainwater harvesting, infiltration wells, retention ponds, trash filters, bioremediation, biofilters, and water quality treatment using constructed wetlands. Meanwhile, the local government of Karawang Regency does not yet have the infrastructure to implement eco-drainage. After conducting an analysis, it was determined that among the 7 elements of eco-drainage, rainwater harvesting is the most needed to address the issues of flooding and drought in the Karawang area. The research results also include calculations and explanations regarding the Eco drain facilities for rainwater collection on a land scale and environmental/community storage tanks, as well as the quality of rainwater in Indonesia.